2018
DOI: 10.3390/ijms19102943
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Expression Patterns and Function of Two cxcr4 Paralogs in Hermaphroditic Epinephelus coioides

Abstract: Chemokine receptor Cxcr4 evolved two paralogs in the teleost lineage. However, cxcr4a and cxcr4b have been characterized only in a few species. In this study, we identified two cxcr4 paralogs from the orange-spotted grouper, Epinephelus coioides. The phylogenetic relationship and gene structure and synteny suggest that the duplicated cxcr4a/b should result from the teleost-specific genome duplication (Ts3R). The teleost cxcr4 gene clusters in two paralogous chromosomes exhibit a complementary gene loss/retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 104 publications
(144 reference statements)
2
8
0
Order By: Relevance
“…In gibel carp, both paralogous and homoeologous pairs of cxcr4b and cxcl12a show dynamic and differential expression patterns and antiviral responses. Our results indicate that cxcr4bs and cxcl12as should play a dominant role in immune response and confirm the specific ligand-receptor recognitions of Cxcl12b and Cxcr4a ( 48 , 70 ). Although derived from the common ancestor ( 71 ), the expression patterns of duplicated genes evolved divergently after separation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In gibel carp, both paralogous and homoeologous pairs of cxcr4b and cxcl12a show dynamic and differential expression patterns and antiviral responses. Our results indicate that cxcr4bs and cxcl12as should play a dominant role in immune response and confirm the specific ligand-receptor recognitions of Cxcl12b and Cxcr4a ( 48 , 70 ). Although derived from the common ancestor ( 71 ), the expression patterns of duplicated genes evolved divergently after separation.…”
Section: Discussionsupporting
confidence: 77%
“…More abundant Cgcxcr4a-A transcripts than Cgcxcr4a-B were detected in head kidney, kidney, gill and heart, while reversely differential expression patterns were observed in spleen, thymus, and intestine ( Figure 3A). Consistent with the specific chemotactic interaction of grouper Cxcr4b-Cxcl12a (48), Cgcxcl12a was the mainly expressed paralog in most analyzed immune-related tissues, as well as Cgcxcr4b (Figure 3B). Except in intestine and brain, Cgcxcl12a-B showed significantly higher expression than Cgcxcl12a-A ( Figure 3B).…”
Section: Dynamic and Differential Expression Patterns Of Cxcr4s And Csupporting
confidence: 74%
“…One microgram plasmids were transfected into HEK293T cells. The cell culture, transfection, fixation, and nuclear staining with 4′, 6-diamidino-2-phenylindole (DAPI) were performed as previously described ( Lu et al. 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The SDF1/CXCR4 signaling is known to be required for the maintenance of mouse spermatogonial stem cells, and inhibition of CXCR4 signaling increases the responsiveness of the germ cells to RA (Yang et al, 2013 ). In addition, study in Orange-spotted grouper demonstrated that the expression of cxcr4b gene is sharply decreased in mature ovary (Lu et al, 2018 ). In cyp26a1 mutant testis, the orphan nuclear receptor 4A1 ( nr4a1 ) was strongly upregulated.…”
Section: Discussionmentioning
confidence: 99%